Protocol for in vitro germination and micropropagation of Himatanthus Sucuuba (Spruce ex Müll. arg.) Woodson - Sáenz-Ramírez, Lyanna Hellen (2025)
Himatanthus sucuuba is important in folk medicine and is widely used as an antitumor, antifungal, vermifuge and anti-anemic agent1. In this context, the objective of this study was to develop a protocol for in vitro germination and micropropagation of H. sucuuba. The seeds were immersed in a 1.0% (v/v) Cabrio Top solution for one hour on a magnetic stirrer and then in a 0.1% (v/v) diluted NaOCl solution for 30 minutes under agitation, followed by immersion in 70% alcohol for 1 minute. Subsequently, the seeds were rinsed four times with sterile distilled water and then inoculated in MS medium supplemented with the auxins AIA, ANA and AIB at concentrations of 0.0; 1.0; 3.0; 5.0 mg L-1. The experimental design was completely randomized, using 10 treatments with 3 replicates of 10 seeds (n = 30). It was observed that the MS medium supplemented with IAA (5.0 mg L-1) resulted in 80% germination and seedlings with 5.97 cm in height and 4.2 nodal segments. To stimulate rooting, the nodal segments were cut and inoculated in MS medium supplemented with BAP (0.1 mg L-1) and in interaction with the auxins IAA, 2,4-D and ANA, at concentrations of 0.0; 3.0; 5.0 and 8.0 mg L-1 and kept in a growth room at 25 ± 2 °C, with a photoperiod of 16 h. The combination BAP+IAA (0.1 + 8.0 mg L-1) showed the best results with 100% sprouting, 40% callus formation and 30% rooting. In conclusion, in vitro propagation is a promising technique to produce H. sucuuba seedlings, however, hormonal adjustments are necessary.